(untitled) (Revista Argentina de Cirugía, 2026)
Endoscopic retrograde cholangiopancreatography (ERCP) is an invasive procedure for the diagnosis and treatment of biliary tract and pancreatic duct diseases. Proximal and distal stent migration is a rare complication. The paucity of publications on this issue motivated this article. The main aim of this study was to describe two case reports of migration of biliary plastic stents, how they were managed and solved. We believe it is important to emphasize the need for recording and monitoring patients who have undergone biliary stent placement, to avoid leaving the stent in situ beyond the recommended time, and thus avoid late complications, since “ignorance is not bliss”.